2012
DOI: 10.2174/092986712803988910
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product MDM2 Inhibitors: Anticancer Activity and Mechanisms of Action

Abstract: The mdm2 oncogene has recently been suggested to be a valuable target for cancer therapy and prevention. Overexpression of mdm2 is often seen in various human cancers and correlates with high-grade, late-stage, and more treatment-resistant tumors. The MDM2-p53 auto-regulatory loop has been extensively investigated and is an attractive cancer target, which indeed has been the main focus of anti-MDM2 drug discovery. Much effort has been expended in the development of small molecule MDM2 antagonists targeting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
57
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 224 publications
(297 reference statements)
0
57
0
Order By: Relevance
“…The chemoresistant cell lines showed upregulation of MDM2 (significant in HLaC79-Tax, not significant in Hep2-Tax). Qin et al (41) reviewed the role of natural products such as flavonoids and isoflavonoids in inhibiting MDM2 expression. Reduction of MDM2 expression was reached with genistein, apigenin and oroxylin A.…”
Section: Discussionmentioning
confidence: 99%
“…The chemoresistant cell lines showed upregulation of MDM2 (significant in HLaC79-Tax, not significant in Hep2-Tax). Qin et al (41) reviewed the role of natural products such as flavonoids and isoflavonoids in inhibiting MDM2 expression. Reduction of MDM2 expression was reached with genistein, apigenin and oroxylin A.…”
Section: Discussionmentioning
confidence: 99%
“…33). Such inhibition requires wild-type p53 expression in cancer cells 34,35 . Considering that the majority (50-75%) of breast cancers harbour mutant p53 and have high levels of MDM2, these MDM2 inhibitors are expected to have low or no efficacy against these types of breast cancer 36 .…”
mentioning
confidence: 99%
“…28 Therefore, it has been suggested that MDM2 is a promising target for the treatment of human cancers, regardless of the p53 status in the tumor cells. 10-12,15-17,21,22,29 …”
mentioning
confidence: 99%